2023
DOI: 10.1159/000528922
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Futile Reperfusion following Endovascular Treatment in Acute Ischemic Stroke due to Large Vessel Occlusion

Abstract: <b><i>Background:</i></b> Futile reperfusion (FR) is becoming an urgent issue for acute ischemic stroke patients who underwent endovascular treatment (EVT). Although the recanalization rate has improved after EVT, it is far from translating to increased tissue reperfusion and functional independence. <b><i>Summary:</i></b> Many underlying mechanisms including the “no-reflow” phenomenon, poor collateral flow, venous dysfunction, and inflammation were proposed, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…To date, the mechanisms of futile recanalization are poorly understood (Deng et al, 2022). No-reflow phenomenon and inflammatory responses are thought to be important mechanisms (Deng et al, 2022;Wang & Xiong, 2023). The no-reflow phenomenon is currently believed to reflect a compromise of the microvascular system, secondary to the dysfunction of endothelia and luminal clogging by leukocytes and microthrombi (Dalkara & Arsava, 2012;Ng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the mechanisms of futile recanalization are poorly understood (Deng et al, 2022). No-reflow phenomenon and inflammatory responses are thought to be important mechanisms (Deng et al, 2022;Wang & Xiong, 2023). The no-reflow phenomenon is currently believed to reflect a compromise of the microvascular system, secondary to the dysfunction of endothelia and luminal clogging by leukocytes and microthrombi (Dalkara & Arsava, 2012;Ng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that high FAR could predict the occurrence of no-reflow phenomenon in patients with myocardial infarction undergoing primary percutaneous coronary intervention (Zhao et al, 2019). As no-reflow phenomenon and inflammatory response are proposed underlying mechanisms of futile recanalization (Deng et al, 2022;Wang & Xiong, 2023), FAR might also be a potential indicator of futile recanalization in acute ischemic stroke patients. This study aims to evaluate whether postoperative FAR could act as an indicator of futile recanalization in patients with successful thrombectomy.…”
Section: Introductionmentioning
confidence: 98%
“…With the advancements in interventional devices and recanalization techniques, the success rate of EVT now stands at 80%–90 %. However, postoperative reperfusion injury continues to be a prevalent concern leading to early complications [e.g., symptomatic intracranial hemorrhage (sICH)] and neurological deterioration, which can ultimately affect long-term clinical outcomes [ [5] , [6] , [7] ]. Additionally, the invasive nature of EVT may cause vascular wall injury (VWI), which can result in peri-interventional hemorrhagic and ischemic complications, ultimately reducing treatment efficacy and clinical outcomes [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%
“…A lesson learned from the first decade of EVT is that successful recanalization is not a synonym of favourable outcome. A great proportion of patients (32.4%–69.6%) showing an angiographically accomplished result at the end of the procedure still present with unfavourable clinical outcome [4]. This has led to the term clinically ineffective reperfusion (CIR).…”
Section: Introductionmentioning
confidence: 99%